Answer:
(-2,2)
Step-by-step explanation:
Let's find the answer.
Because a tangent line for a parabola function is equal to 0 only at its vertex then:
[tex]f(x)=(x+2)^{2}+2[/tex]
[tex]f'(x)=2*(x+2)[/tex]
[tex]f'(x)=2x+4[/tex] so then:
[tex]f'(x)=0[/tex] when
[tex]0=2x+4[/tex]
[tex]-2=x[/tex]
For x=-2 f(x) is:
[tex]f(x)=(x+2)^{2}+2[/tex]
[tex]f(1)=(-2+2)^{2}+2[/tex]
[tex]f(x)=2[/tex]
In conclusion, the vertex of the given parabola is (-2,2), so the answer is C. Although in your answer is reported as (-2.2) but I think was a typing mistake.